A tailored passive driver for liver MRE in pediatric patients - Lorton, Orane; Toso, Seema; El-Begri Talbi, Hayat; Anooshiravani, Mehrak; Poletti, Pierre-Alexandre; Hanquinet, Sylviane; Salomir, Rares (Frontiers in Pediatrics, 2022)
Objectives – Magnetic resonance elastography (MRE) is increasingly used in the pediatric population for diagnosis and staging of liver fibrosis. However, the MR-compatible driver and sequences are usually those used for adult patients. Our feasibility study aimed to adapt the standardized adult MRE passive driver and vibrational parameters to a pediatric population. Methods – We designed an elliptic passive driver shaped on a torus equipped with an elastic membrane and adapted to children’s morphologies. As a first step, 8 children (aged 8-18 years) were enrolled in a prospective pilot study aiming to determine the threshold vibrational amplitude for MRE using the custom passive driver, based on phase aliasing assessment and occurrence of signal void artefacts on magnitude MR images. In a second step, the practicality and the consistency of the custom driver was assessed in a further 11 pediatric patients (aged 7-18 years). In a third step, we compared our custom driver versus the commercial driver on 6 adult volunteers, in terms of the reliable region of interest area within the acquired MRE slices, the shear wave maps quality, and measured stiffness values obtained. Results – Based on pediatric patient data, the threshold vibrational amplitude expressed as percentage of maximum output was found to be 0.4 and 1.1 times the body weight [kg] at frequencies 40Hz and 60Hz, respectively. In comparison to the commercial passive driver, the custom driver improved 3-fold the contact with the body surface, also enabling a more comfortable examination as self-assessed by the volunteers. Conclusions – Our custom driver was more comfortable for the volunteers, and was able to generate more homogenous shear waves, yielding larger usable hepatic area, and more reliable stiffness values.